Qualitative phytochemical analysis and antimicrobial activity of fllicium verum against foodborne pathogens / Siti Nasuha Abd Hadi - Abd Hadi, Siti Nasuha (2015)
Illicium verum or star anise was a commonly used spice with many usages especially in cooking. The usages of star anise also broaden to the entire world due to its medicinal values. Nowadays, there were increasing in the incidence of food- borne diseases caused by pathogenic microorganism thus increasing community concern on food safety. Chemical preservatives that were known to be toxic were widely used in foods. In addition, artificial antimicrobial or antibiotics that might cause side effects to the consumers were commonly used to treat food- borne diseases. The aim of this study was to evaluate antimicrobial activity of Illicium verum extract against food borne pathogens and to investigate phytochemical compounds found in Illicium verum. In order to evaluate the antimicrobial activity of Illicium verum extract against food borne pathogens, three methods were performed; antimicrobial susceptibility testing (AST) by disc diffusion method, determination of minimum inhibitory concentration (MIC) by using broth microdilution method and determination of minimum bactericidal concentration (MBC) by sub- culturing suspension in well onto Tryptic Soy Agar media. The phytochemical compounds were screened by using several standardized methods in which the results were interpreted basically based on colour changes and precipitation of the chemical reagents. The results showed that the sensitivity of both gram positive and gram negative bacteria towards the extract almost similar. The largest diameter zone of inhibition was shown by S. aureus and E.coli followed by S. typhimurium. The smallest zone of inhibition was shown by B. cereus. The zones of inhibition shown by all bacteria were considered significant because the p- value was less than 0.05. For the qualitative analysis of the phytochemical compounds, all the tested compounds; glycosides, phenols, alkaloids, tannins, and terpenoids were found present in the Illicium verum extract. In conclusion, the methanolic extract of Illicium verum had antimicrobial activity against selective food borne pathogens and had the value to become a replacement of synthetic chemical in food preservative and a new natural antimicrobial that was susceptible to food borne pathogens. Moreover, all the tested phytochemical compounds which had been reported contributed in the antimicrobial activity of the Illicium verum extract were present in the extract.